Drivers of Zero-Waste Purchase Decisions : The Mediating Role of the Theory of Planned Behavior - Yadav, Nidhi; Sijoria, Charu (Indian Journal of Marketing, 2024)
Purpose : This study aimed to examine the mediating role of three antecedents of the theory of planned behavior (TPB) between the new environmental paradigm (NEP) and purchase intention via extending the TPB and stimulus-organism-response (S-O-R) paradigm. Methodology : A self-administered questionnaire collected data from 239 individuals with prior knowledge of ZW products. Confirmatory factor analysis (CFA) was employed in SPSS AMOS 21 to examine the validity and reliability of the study. The bootstrapping method was used with structural equation modeling (SEM) to analyze the suggested framework and hypotheses. Findings : NEP positively influenced the purchase intention of ecologically concerned Indian consumers. The attitude (ATT) and perceived behavioral control (PBC) partially mediated the association between NEP and purchase intention. However, the mediating role of subjective norms (SNs) was non-significant. Practical Implications : This studyâ€™s empirical findings could assist interested academicians, policymakers, and marketers attain â€œresponsible consumption and production,â€ the 12th sustainable development goal. Originality : This study integrated the S-O-R model and TPB, significantly contributing to the current knowledge of ZW lifestyle. The proposed framework incorporated NEP, which further enhanced the understanding of TPB. This research thoroughly investigated the TPB mediation function in bridging the gap between NEP and customersâ€™ intention to purchase ZW products.